단어 단위 측정에 의한 정상 아동과 기능적 조음음운장애 아동 간 음운 특성 비교 - 김영은(Young Eun Kim); 석동일(Dong Il Seok) (언어치료연구, 2007)
이 연구는 단어 단위 측정에 의한 정상 및 기능적 조음음운장애 아동의 음운 특성을 알아보기 위해 실시하였으며, 두 집단 간의 단어 단위 측정치를 비교하였고, 단어 단위 측정치 하위 항목별 간 상관관계를 분석하였다. 이 연구에는 만 5세에서 6세까지의 정상 아동 11명, 기능적 조음음운장애 아동 11명, 총 22명을 연구대상으로 하였다. 연구 결과는 다음과 같다. 첫째, 정상 아동과 기능적 조음음운장애 아동의 단어 단위 측정치(단어 단위 정확도, 명료도, 복잡도, 변화도)에서 유의한 차이를 나타내었다. 둘째, 정상 아동의 단어 단위 측정치는 5세, 6세 연령별 간에 통계적으로 유의미한 차이를 나타내지 않았다. 셋째, 단어 단위 측정으로 분석된 측정치 하위 항목 간의 상관관계는 단어 단위 변화도를 제외한 모든 하위 항목간의 상관성이 유의미하였다. 정상 아동과 기능적 조음음운장애 아동 모두 3가지 단어 단위 측정치(단어 단위 정확도, 명료도, 복잡도)간의 강한 정적 상관을 나타내었으나, 변화도와 다른 측정치와의 상관관계는 유의미하지 않았다. 넷째, 기능적 조음음운장애 아동의 그림 자음 검사의 자음 정확도와 3가지 단어 단위 측정치 하위 항목(단어 단위 정확도, 명료도, 복잡도)간에 유의미한 상관성이 있었지만, 자음 정확도와 단어 단위 변화도 간의 상관은 유의미하지 않았다. The purpose of this study was to compare between normal children and functional articulation phonological disorders in measure of whole-word. The subjects who participated in the experiment were 11 functional articulation phonological disorders(5-6 years old), 11 subjects of normal children(5-6 years old). By each sampling 80～100 utterances were gathered and 50 utterances were analyzed with measure of whole-word. The results of this study are following. First, there were significant differences between normal children and functional articulation phonological disorders in whole-word correctness, whole-word complexity, whole-word intelligibility, whole-word variability. Second, there were no significant differences between 5 years old and 6 years old normal children in whole-word correctness, whole-word complexity, whole-word intelligibility, whole-word variability. Third, In both normal children and functional articulation disorders, Pearson correlation analysis of measurements of whole-word showed a high positive correlation in measurements of whole-word(whole-word correctness, whole-word complexity, whole-word intelligibility), except for whole-word variability. Forth, there were high positive correlation between PCC(Percentage of Consonants Correct) and measurements of whole-word(whole-word correctness, whole-word complexity, whole-word intelligibility), except for whole-word variability in functional articulation phonological disorders. KCI Citation Count: 7